Serum levels of vitamin C and vitamin D in a cohort of critically ill COVID-19 patients of a north American community hospital intensive care unit in may 2020. A pilot study (2020)
The COVID-19 pandemic has placed an enormous and growing burden on the population and health infrastructure, warranting innovative ways to mitigate risk of contracting and developing severe forms of this disease. A growing body of literature raises the issue of Vitamin C and Vitamin D as a risk-assessment tool, and therapeutic option, in COVID-19.